Women in ancient Egypt : revisiting power, agency, and autonomy - Ayad, Mariam F., (The American University in Cairo Press, 2022)
"There has been considerable scholarship in the last fifty years on the role of ancient Egyptian women in society. With their ability to work outside the home, inherit and dispense of property, initiate divorce, testify in court, and serve in local government, Egyptian women exercised more legal rights and economic independence than their counterparts throughout antiquity. Yet, their agency and autonomy are often downplayed, undermined, or outright ignored. In Women in Ancient Egypt, twenty-four international scholars offer a corrective to this view by presenting the latest cutting-edge research on women and gender in ancient Egypt. Covering the entirety of Egyptian history, from earliest times to Late Antiquity, this volume commences with a thorough study of the earliest written evidence of Egyptian women, both royal and non-royal, before moving on to chapters that deal with various aspects of Egyptian queens, followed by studies on the legal status and economic roles of non-royal women and, finally, on women's health and body adornment. Within this sweeping chronological range, each study is intensely focused on the evidence recovered from a particular site or a specific time-period. Rather than following a strictly chronological arrangement, the thematic organization of chapters enables readers to discern diachronic patterns of continuity and change within each group of women."--